Suppression the Disturbance of Robotic Manipulators Based on Nonlinear Disturbance Observer and Fuzzy Logic System - He, Wangyong; Li, Haogui; Wang, Yuanjiang; Liu, Sanqiu (Journal of advanced computational intelligence and intelligent informatics, 2020)
Robotic Manipulators (RM) are nonlinear and coupling system with time-variant and model uncertainties. In addition, RM are subject to different types of disturbances in practice, such as joint frictions, unknown payloads, and interferences from external systems. In this paper, these adverse factors are regarded as disturbance, and classifies them into internal disturbances and external disturbances. In order to achieve high-precision control, a Nonlinear Disturbance Observer (NDO) is designed to suppress external disturbances, and a Fuzzy Logic System (FLS) is designed to compensate internal disturbances. The scheme can effectively suppress the disturbance and improve the control accuracy. The validity of the scheme is shown by computer simulations of a two-link robot manipulator.